Secondary Teachers and Students’ Perspectives towards Online Learning amid the COVID-19 Outbreak - Jariya Thongbunma; Prasart Nuangchalerm; Sirilak Supakam (Universitas Sultan Ageng Tirtayasa, 2021)
In the quarantine time, COVID-19 outbreak cannot stop our learning but it makes school and instructional practices do natural online learning. This research aims to study secondary teachers and students’ perspectives towards online learning amid the COVID-19 outbreak. The respondents were 38 teachers and 212 students from one secondary school, Mahasarakham province, Thailand. Data were collected through online survey in Semester 2 Academic Year 2020. Questionnaires about online learning amid COVID-19 outbreak and online interviewing were used. It found that that teachers had positive perspective towards online learning at high level, but students had their perspective was at low level. It can be concluded that online learning activities may be suitable for readiness students in both methods and tools, the study also need to be discussed by educators and policy maker for helping students meet the goal of curriculum and students’ success.